The Genesis of Direct Negotiation, the Fiscal Envelope and Their Impact on Tribal Land Claim Settlements - Walker, Ranginui (He Pukenga Korero: a journal of Māori studies, 1997)
Keywords: mātauranga māori; national party; parliament; social life and customs; treaty settlements; tāngata whenua

A Traditionalist Approach to Iwi Government - Potiki, Tahu (He Pukenga Korero: a journal of Māori studies, 2000)
Keywords: iwi; mātauranga māori; self-governance; social life and customs; te reo māori; tino rangatiratanga; treaty settlements; tāngata whenua

Restoration of the Tribal Collective: Rebuilding Tribal Capacity Alongside Economic Development - White, Paul (He Pukenga Korero: a journal of Māori studies, 2000)
Keywords: development; economic development; mātauranga māori; social life and customs; treaty settlements; tāngata whenua

An Imbalance of Powers: Maori Land Claims and an Unchecked Parliament - Charters, Claire (Cultural Survival, 2010)
Aotearoa/New Zealand is not known for egregious breaches of indigenous peoples’ rights. Nonetheless, New Zealand’s legal system is ineffective at implementing international and domestic laws that protect the rights of Maori. This has been seen most starkly in the Foreshore and Seabed Act of 2004, which had the effect of extinguishing Maori aboriginal title to the foreshore and seabed areas and was passed despite almost universal Maori opposition.
Keywords: civil Rights; constitution; crown policy; foreshore and seabed act 2004; parliament; tiriti o waitangi/treaty of waitangi; treaty settlements

The Role of Maori women in Treaty Negotiations and Settlements - Rangiheuea, Tania (1995)
Keywords: crown; māori decision making; tino rangatiratanga; treaty settlements; wāhine māori

Integrating Indigenous Knowledge and Freshwater Management: An Aotearoa/New Zealand Case Study - Hudson, Maui; Watene-Rawiri, Erina; Robb, Mahuru; Collier, Kevin; Awatere, Shaun; Harmsworth, Garth; Henry, Jacqueline; Quinn, John; Death, Russell; Hamilton, David; Maru, John (The International Journal of Science in Society, 2016)
Keywords: governance; iwi; kāwanatanga; local government; treaty settlements; water management

Behind the smoke and mirrors of the Treaty of Waitangi claims settlement process in New Zealand: no prospect for justice and reconciliation for Māori without constitutional transformation - Mutu, Margaret (Journal of Global Ethics, 2018)
Governments in New Zealand have legislated a large number of settlements extinguishing many hundreds of claims taken by Māori against the Crown for breaches of the country’s founding document, Te Tiriti o Waitangi. They portray settlements as a great success for Māori and the Crown. Māori disagree. Settlements are government-determined and imposed on Māori using a smoke and mirrors approach that masks successive governments’ true intentions: to claw back Māori legal rights; to extinguish all claims; and to maintain White control over Māori. In short, to uphold the Doctrine of Discovery in further breach of Te Tiriti o Waitangi. Māori claimants and negotiators report being enticed into the process by false promises only to become traumatised and disenchanted. Yet many take a pragmatic stance and sign settlements, making the best they can out of a bad deal that goes nowhere near compensating for their actual loss. They know that despite what legislation may say, the settlements are not full, not fair and not final and that, like all previous settlements, they will be revisited. They also know that unless fundamental changes are made to the constitutional makeup of the country, there is no prospect of justice and reconciliation for Māori.
Keywords: colonisation; constitutional transformation; doctrine of discovery; kāwanatanga; tiriti o waitangi/treaty of waitangi; trauma; treaty settlements; waitangi tribunal

The treaty claims settlement process in New Zealand and its impact on Māori - Mutu, Margaret (2019)
This article considers research conducted on the impact of the Crown’s treaty claims settlement policy on Māori in New Zealand. It provides a brief background to the Treaty of Waitangi and the subsequent British colonisation process that relied on the Doctrine of Discovery in breach of the treaty. It outlines how colonisation dispossessed Māori of 95 percent of their lands and resources, usurped Māori power and authority and left them in a state of poverty, deprivation and marginalisation while procuring considerable wealth, prosperity and privilege for British settlers. The work of the Waitangi Tribunal, the commission of inquiry set up to investigate those breaches, is considered, as is the Crown’s reaction to the 1987 Lands case in developing its treaty claims settlement policy. The Crown unilaterally imposed the policy despite vehement opposition from Māori. Since 1992, it has legislated more than seventy ‘settlements’. The research shows that overall, the process has traumatised claimants, divided their communities, and returned on average less than one percent of their stolen lands. Proposals for constitutional transformation have drawn widespread support from Māori as a solution to British colonisation. United Nations treaty-monitoring bodies have recommended that the government discuss this with Māori
Keywords: colonisation; constitutional transformation; crown policy; law; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

‘To honour the treaty, we must first settle colonisation’ (Moana Jackson 2015): the long road from colonial devastation to balance, peace and harmony - Mutu, Margaret (Journal of the Royal Society of New Zealand, 2019)
Māori leaders in New Zealand continue the battle to end British colonisation. The aim is to restore the balance between Māori and the Crown guaranteed in the treaty that Māori and the British Crown agreed to in 1840 so that we can live in peace and harmony. Early European visitors subjected our ancestors to numerous atrocities. Relying on the Doctrine of Discovery, they illegitimately usurped our power and dispossessed us, leaving us in a state of poverty, deprivation and marginalisation. They fabricated myths to justify their criminal activities, set up an illegitimate parliament with unfettered powers, passed laws legalising their crimes and then covered it up with amnesia. They established the Waitangi Tribunal in 1975 to inquire into breaches of the treaty, not realising that it would dismantle the myths and look beneath the amnesia. Governments then instigated the ‘treaty claims settlement’ process to extinguish all Māori claims, remove Māori rights and entrench colonisation. Research undertaken has shown that Māori loathe this process and do not accept that settlements are full and final. Research on constitutional transformation has identified a possible solution. The first step towards that goal involves implementing the United Nations Declaration on the Rights of Indigenous Peoples.
Keywords: UNDRIP; colonisation; colonisation myths; constitutional transformation; crown; kāwanatanga; māori rights; oral history; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; treaty breaches; treaty settlements; waitangi tribunal

Neo-Liberal Settlements: From Adam Smith to Treaty Settlements - Tau, Te Maire (NZ Journal of History, 2015)
Keywords: kāwanatanga; sovereignty; treaty settlements

Diverting the Sword of Damocles: Why Did the Crown Choose to Settle Māori Historical Treaty Claims? - McDowell, Tiopira (Australian Journal of Politics & History, 2018)
Keywords: crown; treaty settlements

Reconciliation: The Political Theological Nexus in Australasian Indigenous Public Policy - O’Sullivan, Dominic (International Journal of Public Theology, 2010)
Reconciliation brings together Christological and anthropological dimensions of human thought to illustrate the nexus between religious principles and political means. For the state reconciliation is concerned with social cohesion and political stability. For the church, it extends the sacramental notion of reconciliation between God and penitent to public relationships. This article examines Roman Catholic contributions to secular reconciliation debates. It shows how religious precepts create moral imperatives to engagement with secular discourses as a necessary element of Christian mission. It also argues that the church’s role in the disruption of indigenous societies creates an additional moral imperative to engage in reconciliation as mission and to articulate a Christian vision of indigenous rights.
Keywords: christianity; kāwanatanga; open access version available; reconciliation; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty settlements